Direct torque control of induction motor based on double-power-super-twisting sliding mode speed control for electric vehicle applications - Mencou, Siham; Yakhelf, Majid Ben; Tazi, Elbachir (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
To improve the performance and energy efficiency of the direct torque control of induction motors used in electric vehicles a double-power-super-twisting sliding mode control (DPSTA SMC) strategy has been introduced in the closed speed loop. This strategy is based on the novel double-power-super-twisting algorithm (DPSTA), which combines the performance of the traditional super-twisting algorithm (STA) with the double power reaching law (DPRL). The stability of the algorithm has been proven using a quasi-quadratic Lyapunov function. The performances of the proposed DPSTA SMC controller have been compared with that of PI, fuzzy logic, and STA SMC controllers. Detailed simulations are carried out using MATLAB/Simulink software. The results demonstrate that this approach effectively improves tracking accuracy, system robustness and energy efficiency, while significantly reducing the chattering phenomenon.